Staff Member Reactions to Same-Gender, Resident-to-Resident Sexual Behavior Within Long-Term Care Facilities. Issue 11 (19th September 2017) - Ahrendt, Andrew; Sprankle, Eric; Kuka, Alex; McPherson, Keagan
ABSTRACT: The current study assesses ageism and heterosexism relating to older adult sexual activity within long-term care facilities. To assess caregiver reactions, 153 residential care facility staff members read one of three vignettes. Each vignette described a scenario in which a staff member walks in on two residents (male/female, male/male, or female/female) engaging in sexual activity. Although no main effects were discovered for vignette type, exploratory analyses revealed that the facility where participants were employed was significantly related to their ratings of approval. Furthermore, an interaction effect between vignette and facility types was also discovered for caregivers' approval of sexual activity among residents. Additionally, a strong overall approval rating of older adult sexuality was reported by staff members. The results of this study warrant that further research is necessary regarding older adults' perception of caregiver bias, as well as further investigation of caregivers' perceptions of older adults' sexual activity.